Comparative analysis of Volume Controlled Ventilation (VCV), Pressure Controlled Ventilation (PCV) and Pressure-Regulated Volume-Control (PRVC) ventilatory modes on ventilatory mechanics, mechanical ventilation time, ICU hospitalization and survival in neurological patients (Research, Society and Development, 2022)
Objectives: To compare the outcome of VCV, PCV and PRVC ventilation modes in relation to ventilatory mechanics, mechanical ventilation time, ICU length of stay and survival in neurological patients. Methods: Randomized cohort study comparing three ventilation modalities VCV, PCV and PRVC in neurological patients diagnosed with ischemic or hemorrhagic stroke and TBI, mechanically ventilated and admitted to the ICU. The mechanical ventilator was adjusted according to the selected mode and with ventilation parameters adjusted to maintain a tidal volume of 6 to 8 ml/kg and blood gas parameters within the normal range. Demographic data, hemodynamic, blood gas and ventilatory parameters and the APACHE II, RASS and Glasgow scales were collected. At the end of the protocol, mortality/survival data, length of stay in the ICU and discharge from the unit were recorded. Results: The PVC group had a longer time of permanence in assisted controlled ventilation in relation to the VCV and PRVC groups (p=0.04). In addition, the PCV group had longer mechanical ventilation (p=0.002), longer ICU stay (p=0.01). Still, there was no difference between the groups in terms of survival, the VCV and PRVC groups showed a trend towards survival when compared to PCV (p=0.4). Finally, there was no difference between the groups in terms of clinical characteristics, ventilatory mechanics and blood gases. Conclusion: Neurological patients should be mechanically ventilated preferably in VCV and PRVC mode, as these modes have advantages over PCV mode in neurological patients.